Design and Implementation of Generics for the .NET Common Language Runtime - Kennedy, Andrew; Syme, Don (Programming Language Design and Implementation, 2001)
The Microsoft .NET Common Language Runtime provides a shared type system, intermediate language and dynamic execution environment for the implementation and inter-operation of multiple source languages. In this paper we extend it with direct support for parametric polymorphism (also known as generics), describing the design through examples written in an extended version of the C# programming language, and explaining aspects of implementation by reference to a prototype extension to the runtime. Our design is very expressive, supporting parameterized types, polymorphic static, instance and virtual methods, “F-bounded” type parameters, instantiation at pointer and value types, polymorphic recursion, and exact run-time types. The implementation takes advantage of the dynamic nature of the runtime, performing justin-time type specialization, representation-based code sharing and novel techniques for efﬁcient creation and use of run-time types. Early performance results are encouraging and suggest that programmers will not need to pay an overhead for using generics, achieving performance almost matching hand-specialized code.